Study of Growth Differentiation Factor 15(GDF15) and Some Biochemical Parameters in Multiple Myeloma Patients Subjected to Chemotherapy with Added Paroxetine in-Vitro - A. H. Al-Timeeme, Zahraa; Kadhum H. Alhashemi, Wisam; Sahham Naji, Alaadin; Fadhil Neama, Ahmed (Al-Nahrain Journal of Science, 2020)
Introduction: Multiple myeloma (MM) is a cancer that shapes from excessive amounts of a monoclonal immunoglobulin (Ig) which accumulate in the bone marrow, where they assemble healthy blood cells.Materials and Methods: there are two lines was dealt with it: For in vivo the study involved 80 multiple myeloma Patients grouped according sessions of chemotherapy (new diagnosis without treatment, and patients subjected to six sessions of chemotherapy treatment) for each group the following biochemical parameters were measured Growth differentiation factor 15 (GDF-15), albumin, calcium, C-reactive protein(CRP) in serum. In vitro was measured Growth differentiation factor 15 on RPMI 8226 cell line of multiple myeloma with mixture of chemotherapy (Mix1) and with combination of standard chemotherapy and antideportation paroxetine (Mix2).Results: In serum Growth differentiation factor 15 was showed significantly increased (p